III-Nitride Deep UV LED Without Electron Blocking Layer - Zhongjie Ren; Yi Lu; Hsin-Hung Yao; Haiding Sun; Che-Hao Liao; Jiangnan Dai; Changqing Chen; Jae-Hyun Ryou; Jianchang Yan; Junxi Wang; Jinmin Li; Xiaohang Li (IEEE Photonics Journal)
AlGaN-based deep UV (DUV) LEDs generally employ a p-type electron blocking layer (EBL) to suppress electron overflow. However, Al-rich III-nitride EBL can result in challenging p-doping and large valence band barrier for hole injection as well as epitaxial complexity. As a result, wall plug efficiency (WPE) can be compromised. Our systematic studies of band diagram and carrier concentration reveal that carrier concentrations in the quantum well and electron overflow can be significantly impacted because of the slope variation of the quantum barrier (QB) conduction and valence bands, which in turn influence radiative recombination and optical output power. Remarkably, grading the Al composition from 0.60 to 0.70 for the 12-nm-thick AlGaN QB of the DUV LED without the EBL can lead to 13.5% higher output power and similar level of overflown electron concentration (∼1 × 1015/cm3) as opposed to the conventional DUV LED with the p-type EBL. This paradigm is significant for the pursuit of higher WPE or shorter emission wavelength for DUV LEDs and lasers, as it provides a new direction for addressing electron overflow and hole injection issues.